PENINGKATAN KUALITAS PEMBELAJARAN MELALUI ANALISIS INDIKATOR RAPOR PENDIDIKAN DI SD NEGERI 6 BANDA ACEH - Mudassir (Lembaga Riset dan Inovasi Kreyat Center, 2025)
This study aims to analyze the efforts to improve the quality of learning at SD Negeri 6 Kota Banda Aceh based on the evaluation results of the 2025 Education Report. The background of this research is the relatively low learning quality score in the previous year, which indicates the need for strategic interventions and continuous improvement. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observations, and documentation studies of the 2024 and 2025 Education Reports. The research subjects consist of the school principal, teachers, and education supervisors. The findings show an increase in the learning quality score from 60.87 to 68, with significant improvements in three main indicators: classroom management (from 66.61 to 71.47), psychological support (from 62.54 to 69.17), and teaching methods (from 53.45 to 66). These improvements were achieved through collaborative clinical supervision, teacher capacity building through professional learning communities, and the implementation of student-centered learning strategies. The study’s findings indicate that data-based and collaborative approaches are effective in enhancing the quality of the learning process in primary schools. The conclusion of this research is that the optimal utilization of the Education Report, transformative school leadership, and the active involvement of teachers in professional development can serve as key factors in sustainably improving learning quality.